Effect of 20% Forest Honey on the Salivary Flow Rate in Menopausal Women with Xerostomia - Darwis, Aida Fadhilla; Siregar, Darmayanti (Dentika: Dental Journal, 2023)
The decrease in the production of estrogen and progesterone hormones in menopausal women may result in a condition called xerostomia, which is characterized by the subjective perception of dry mouth. This condition can be treated by using a chemical or mechanical stimulus. Therefore, the aims of this study were to identify the chemical content of forest honey as well as to determine the effect of its usage as a 20% mouth rinse on the salivary flow rate in menopausal women with xerostomia at RSGM Universitas of Sumatera Utara. This is an experimental study, which was designed using a single-blind randomized pretest-posttest control group. The inclusion criteria were menopausal women aged 40-65 years old with xerostomia, were not undergoing chemotherapy or radiotherapy treatment for the neck and head, had no systemic diseases, such as uncontrolled diabetes mellitus and kidney failure, and not consuming medication that could affect the normal saliva function. Subjects who were not cooperative during the study procedures were excluded. The sample population consisted of 30 menopausal women with xerostomia, which were divided into two groups. The first group was treated by asking them to gargle with 20% honey solution, while the second group, which served as a control used distilled water. Saliva was collected before and after treatment into a pot for 5 minutes using the spitting method, and the data collected were analyzed with T-test. The results showed that forest honey was rich in diastase enzyme and it increased the salivary flow rate, with p-value=0.000<0.05. Based on these findings, the use of 20% honey solution had a significant effect in increasing the salivary flow rate in menopausal women with xerostomia.